Pengaruh Green Product Dan Label Halal Terhadap Minat Beli Produk Kecantikan Kedas Beauty Masyarakat Muslim Kota Jambi - Ayu Putri Lestari; Titin Agustin Nengsih; Neneng Sudharyati (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
At this time, the development of various brands in cosmetic products is very diverse. From time to time the number of brands and products in circulation is increasing rapidly so that market competition increases. Everyone has their own choice in consuming the desired product. Green products and halal labels are one of the factors that can influence consumer buying interest in making a purchase. This study aims to determine and analyze the effect of green products and halal labels on interest in buying kedas beauty products in the Muslim community of Jambi City. The number of samples in this study were 97 people using a non-probability sampling technique, namely purposive sampling. Collecting data through the distribution of questionnaires, observations, interviews and documentation. The results showed that there was a positive and significant influence between green products and buying interest on interest in buying kedas beauty products.